Sedimentary Basins of Indonesia: Outline and Thickness Variation Understanding - Herman Darman; Doddy Yuliong B.A. (Berita Sedimentologi, 2020)
Offshore petroleum exploration in Indonesia began in late 1960’s and thereafter a significant number of seismic data sets were acquired. Based on these data, several basin outline maps were generated such as those published by Hamilton (1974), BEICIP FRANLAP (1992), and Sujanto (1997). Based on these data sets, 60 sedimentary basins were officially recognized by the Government of Indonesia (Sunarjanto et al., 2007 included in 2008 publication). The outlines of the basins were used as a reference by government officials and the petroleum industry. Recently, the Geological Agency published a map which shows 128 sedimentary basin outlines in Indonesia. Unfortunately, these maps were not accompanied with supporting subsurface data.The understanding of those sedimentary basins is very important for petroleum exploration, as they are basically the places to find hydrocarbons. Petroleum potential within a basin is related to its sediment accumulation and tectonic history. Critical petroleum system elements such as source rocks, reservoir and seal mainly comprise sedimentary rocks. The order of deposition, quantity of sediments and basin history will control the effectiveness and quantity of hydrocarbon generation in a particular basin.This article will go through the history of various basin outline maps and aim to provide additional information, such as basement depth, to give further detail on the basins in Indonesia. There are some detailed maps which show the distribution of oil and gas fields, which are obviously related to sediment thickness.